Evaluation of radon adsorption characteristics of a coconut shell-based activated charcoal system for radon and thoron removal applications. (April 2015) - Karunakara, N.; Sudeep Kumara, K.; Yashodhara, I.; Sahoo, B.K.; Gaware, J.J.; Sapra, B.K.; Mayya, Y.S.
Abstract: Radon ( 222 Rn), thoron ( 220 Rn), and their decay products contribute a major fraction (more than 50%) of doses received from ionisation radiation in public domain indoor environments and occupation environments such as uranium mines, thorium plants, and underground facilities, and are recognised as important radiological hazardous materials, which need to be controlled. This paper presents studies on the removal of 222 Rn and 220 Rn from air using coconut shell-based granular activated charcoal cylindrical adsorber beds. Experiments were conducted to evaluate the 222 Rn and 220 Rn adsorption characteristics, and the mitigation efficiency of coconut-based activated charcoal available in India. The performance parameters evaluated include breakthrough time ( τ ) and adsorption coefficient ( K ), and degassing characteristics of the charcoal bed of varying dimensions at different flow rates. While the breakthrough for 222 Rn occurred depending on the dimension of the adsorber bed and flow rates, for 220 Rn, the breakthrough did not occur. The breakthrough curve exhibited a stretched S- shape response, instead of the theoretically predicted sharp step function. The experiments confirm that the breakthrough time individually satisfies the quadratic relationship with respect to the diameter of the bed, and the linear relationship with respect to the length, as predicted in the theory. The K value varied in the range of 2.3–4.12 m 3 kg −1 with a mean value of 2.99 m 3 kg −1 . The K value was found to increase with the increase in flow rate. Heating the charcoal to ∼100 °C resulted in degassing of the adsorbed 222 Rn, and the K of the degassed charcoal and virgin charcoal were found to be similar with no deterioration in performance indicating the re-usability of the charcoal. Highlights: 222 Rn and 220 Rn removal from air using activated charcoal bed is demonstrated. Breakthrough time and adsorption coefficient were evaluated. A sustained mitigation factor exceeding 10 5 was demonstrated for 220 Rn. Degassing characteristics excellently demonstrate the reusability of charcoal. Results would find application in designing 220 Rn mitigation systems for workplaces.